High-rate graphite negative electrode material, preparation method thereof and lithium ion battery
By performing surface oxidation treatment and high-temperature treatment on the raw material coke, a hard carbon layer is formed in situ to coat graphite, and a graphite negative electrode material co-modified by asphalt materials is formed, which solves the problem of poor coating uniformity in traditional methods and significantly improves the ratio, circulation and first-effect performance of the material.
Patent Information
- Application Number
- CN202411475382.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-03-11
AI Technical Summary
The production method of traditional hard carbon coated graphite negative electrode materials leads to poor coating uniformity, which limits its performance improvement.
After the surface oxidation treatment of the raw material coke, high-temperature carbonization and graphitization are carried out, a hard carbon layer is formed in situ to coat graphite, and a graphite negative electrode material co-modified by soft and hard carbon is formed in combination with asphalt materials.
The rate performance, cycle performance and first-effect performance of graphite negative electrode materials are improved, the structural strength and uniformity of the coating are enhanced, and the rapid embedding and deintercalation of lithium ions are promoted.
Smart Images

Figure BDA0005095948820000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of negative electrode materials for lithium ion batteries, and in particular relates to a high-rate graphite negative electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] As the main material of the battery, the main function of the negative electrode material during the charging process is to store lithium. The lithium insertion speed of the negative electrode material is one of the most important factors affecting the fast charging ability of the battery. Graphite material has good chemical stability and electrical properties, and is still the mainstream negative electrode material on the market. However, due to its sheet structure, lithium ions can only be inserted into the end surface, not the base surface, so the lithium insertion speed of conventional graphite materials is slow.
[0003] At present, the most common method to improve the fast charging performance of graphite is to coat the graphite surface with a layer of soft carbon. The interlayer spacing of soft carbon is larger than that of graphite, the degree of disorder between layers is higher, and there are more lithium insertion paths. It can guide the lithium ions on the graphite base surface to the end surface for embedding, thereby improving the fast charging performance of graphite. The method that is currently emerging to provide graphite fast charging performance is hard carbon coating. The interlayer spacing and degree of disorder of hard carbon are higher than those of soft carbon, and the fast charging performance is better than that of soft carbon coating. However, the traditional method of making hard carbon-coated graphite negative electrode materials is to mix graphite particles with hard carbon coating agents and then carbonize, mix and screen them to finally obtain negative electrode materials. Although the hard carbon-coated graphite negative electrode materials obtained in this way can improve their fast charging performance to a certain extent, the coating uniformity of the hard carbon coating agent added later is poor, and the performance improvement is limited. Summary of the invention
[0004] Based on the above technical problems, the present invention provides a high-rate graphite negative electrode material, a preparation method thereof and a lithium-ion battery, wherein the raw coke is subjected to surface oxidation treatment and then subjected to high-temperature carbonization and graphitization, thereby forming an in-situ hard carbon layer coating on the surface of the obtained graphite, which can not only further improve the rate performance of the obtained graphite negative electrode material, but also take into account the cycle performance and first-effect performance.
[0005] The present invention provides a method for preparing a high-rate graphite negative electrode material, comprising the following steps:
[0006] S1. After the raw coke is subjected to oxidation treatment, the surface of the raw coke is oxidized to obtain oxidized raw coke;
[0007] S2, pre-carbonizing and graphitizing the oxidized raw coke to form graphite with a hard carbon layer on the surface, thereby obtaining a graphite negative electrode precursor;
[0008] S3, mixing the graphite negative electrode precursor with the asphalt material, and then carbonizing and sintering, so that a soft carbon coating layer is further formed on the surface of the hard carbon coating layer, and a soft and hard carbon coated graphite material is obtained, which is the graphite negative electrode material.
[0009] In the present invention, the raw coke is first subjected to an oxidation treatment, and the surface layer of the raw coke is oxidized, thus forming a difference from the inside. After high-temperature carbonization and graphitization sintering, the inside of the raw coke is converted into graphite, and the surface is converted into a hard carbon layer due to pre-oxidation, thus obtaining a graphite negative electrode coated with a hard carbon layer. Compared with the conventional hard carbon layer-coated graphite negative electrode formed by mixing the raw coke with a hard carbon coating agent and carbonizing the same, the hard carbon coating layer of the present invention is directly formed in situ, so the structural strength, consistency and uniformity are better, and the coating layer is also denser, which not only helps to improve the cycle stability of the obtained graphite negative electrode, but also facilitates the rapid deintercalation of lithium ions, which can greatly improve the rate performance and fast charging performance of the obtained graphite negative electrode. In addition, the present invention further realizes the coating of the soft carbon layer by mixing asphalt materials, so that the first efficiency and energy density of the upper hard carbon layer are slightly lower, so that the first efficiency of the final graphite negative electrode material is improved, thereby achieving the purpose of taking into account high rate performance, excellent cycle performance and high energy density at the same time.
[0010] Preferably, in step S1, the raw coke is at least one of needle coke, petroleum coke, asphalt coke or calcined coke; and the oxidant is at least one of hydrogen peroxide, potassium permanganate, sodium hypochlorite or manganese dioxide.
[0011] Preferably, in step S1, the oxidation treatment temperature is 60-90°C and the time is 1-3h.
[0012] Preferably, in step S2, the pre-carbonization sintering temperature is 800-1000°C, the time is 3-6h, and the heating rate is 1-5°C / min; the graphitization sintering temperature is 2800-3000°C, and the time is 4-8h;
[0013] Preferably, the pre-carbonization and graphitization sintering are performed under the protection of nitrogen or argon.
[0014] Preferably, in step S3, the asphalt material is at least one of coal asphalt, petroleum asphalt or mesophase asphalt;
[0015] Preferably, the mass ratio of the graphite negative electrode precursor to the asphalt material is 93-98:2-7.
[0016] Preferably, in step S3, the carbonization sintering temperature is 1000-1200°C, the time is 4-8h, and the heating rate is 1-5°C / min.
[0017] Preferably, before step S2, the method further comprises chemically grafting polystyrene boric acid onto the surface of the oxidized raw material coke;
[0018] Preferably, the “chemically grafting polystyrene boric acid on the surface of oxidized raw coke” specifically comprises: subjecting the oxidized raw coke to a condensation reaction with 2-bromoisobutyryl bromide to obtain bromine-functionalized oxidized raw coke, and then subjecting the oxidized raw coke to a surface-initiated free radical polymerization reaction with 4-vinylbenzeneboronic acid to obtain oxidized raw coke with polystyrene boric acid chemically grafted on the surface;
[0019] Preferably, the mass ratio of the oxidation raw material coke to 4-vinylbenzeneboric acid is 100:0.5-2.
[0020] In the present invention, after the raw coke is oxidized, the surface of the obtained oxidized raw coke has oxygen-containing functional groups (-OH or -COOH), which can condense with 2-bromoisobutyryl bromide to form bromine-functionalized oxidized raw coke, and the bromoalkyl groups contained therein can be used as initiators to initiate free radical polymerization through surface initiation, thereby initiating polymerization of 4-vinylbenzeneboronic acid, and finally grafting polystyrene boric acid onto the surface of the raw coke; since polystyrene boric acid, as a resin polymer, can be composited with the surface of the oxidized raw coke to form a hard carbon layer after subsequent graphitization, the defect of forming a hard carbon layer on the surface of the oxidized raw coke is reduced, and the first effect and cycle performance of the obtained graphite negative electrode material are further improved. On the other hand, boron element can be introduced after the graphitization of polystyrene boric acid, and the addition of boron element can catalyze graphitization at high temperature, thereby greatly improving the structure of the hard carbon, and further improving its rate and cycle performance.
[0021] The present invention also provides a high-rate graphite negative electrode material, which is prepared by the above preparation method.
[0022] Preferably, the graphite negative electrode material comprises graphite, a hard carbon layer coated on the surface of the graphite, and a soft carbon layer coated on the surface of the hard carbon layer.
[0023] The present invention also provides a lithium-ion battery, which includes the above-mentioned graphite negative electrode material.
[0024] Compared with the prior art, the present invention has the following technical effects:
[0025] The present invention, without adding any hard carbon coating material, performs surface oxidation on the raw coke before graphitization, so that the obtained graphite surface is in-situ coated with a hard carbon layer, and then a pitch-type soft carbon material is used for coating, thereby forming a graphite negative electrode material co-modified with hard carbon and soft carbon; on the one hand, the hard carbon layer constructs a rapid diffusion channel for lithium ions, and on the other hand, the soft carbon layer can solve the problem that the first efficiency and energy density of the hard carbon layer are slightly low, and the finally obtained graphite negative electrode material has good rate performance and cycle performance. DETAILED DESCRIPTION
[0026] Hereinafter, the present invention will describe the technical solution in detail through specific embodiments, but it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.
[0027] Example 1
[0028] This embodiment provides a method for preparing a high-rate graphite negative electrode material, which specifically includes the following steps:
[0029] (1) 100 g of needle coke was crushed to a particle size D50 of 10 μm, added to 300 mL of H2O2 with a mass concentration of 20%, mixed by magnetic stirring for 1 h, and then placed in a reactor, and then placed in an oven at 80° C. for 2 h. After the mixture was dried, filtered, washed with deionized water, and dried to obtain oxidized needle coke;
[0030] (2) placing the oxidized needle coke in a box-type atmosphere furnace for pre-carbonization sintering, heating the temperature to 900°C at a heating rate of 3°C / min under nitrogen protection, keeping the temperature for 4 hours, and then placing it in a graphitization furnace for high-temperature graphitization at a graphitization temperature of 2900°C for 6 hours to obtain a graphite negative electrode precursor;
[0031] (3) The above-mentioned graphite negative electrode precursor and coal tar powder (D50 is 6 μm) are placed in an agate mortar for mixing and coating, and the mass ratio of the graphite negative electrode precursor to the coal tar powder is 95:5. Then, the mixture is placed in a box-type atmosphere furnace for carbonization sintering. Under nitrogen protection, the temperature is increased to 1150°C at a heating rate of 3°C / min, and the mixture is kept warm for 6 hours. Finally, the mixture is passed through a 325-mesh sieve to obtain the graphite negative electrode material.
[0032] Example 2
[0033] This embodiment provides a method for preparing a high-rate graphite negative electrode material, which specifically includes the following steps:
[0034] (1) 100 g of needle coke was crushed to a particle size D50 of 8 μm, added to 300 mL of H2O2 with a mass concentration of 20%, mixed by magnetic stirring for 1.5 h, and then placed in a reactor. The reactor was then placed in a 60° C. oven for 3 h. After the mixture was dried, filtered, washed with deionized water, and dried to obtain oxidized needle coke;
[0035] (2) placing the oxidized needle coke in a box-type atmosphere furnace for pre-carbonization sintering, heating the temperature to 1000° C. at a heating rate of 1° C. / min under nitrogen protection, keeping the temperature for 3 h, and then placing the oxidized needle coke in a graphitization furnace for high-temperature graphitization at a graphitization temperature of 3000° C. for 4 h to obtain a graphite negative electrode precursor;
[0036] (3) The above-mentioned graphite negative electrode precursor and coal tar powder (D50 is 5 μm) are placed in an agate mortar for mixing and coating, and the mass ratio of the graphite negative electrode precursor to the coal tar powder is 93:7. Then, the mixture is placed in a box-type atmosphere furnace for carbonization sintering. Under nitrogen protection, the temperature is increased to 1000°C at a heating rate of 5°C / min, and the mixture is kept warm for 8 hours. Finally, the mixture is passed through a 325-mesh sieve to obtain the graphite negative electrode material.
[0037] Example 3
[0038] This embodiment provides a method for preparing a high-rate graphite negative electrode material, which specifically includes the following steps:
[0039] (1) 100 g of needle coke was crushed to a particle size D50 of 12 μm, added to 300 mL of H2O2 with a mass concentration of 20%, mixed by magnetic stirring for 1 h, and then placed in a reactor, and then placed in a 90° C. oven for 1 h. After the mixture was dried, filtered, washed with deionized water, and dried to obtain oxidized needle coke;
[0040] (2) placing the oxidized needle coke in a box-type atmosphere furnace for pre-carbonization sintering, heating the temperature to 800° C. at a heating rate of 5° C. / min under nitrogen protection, keeping the temperature for 6 h, and then placing the oxidized needle coke in a graphitization furnace for high-temperature graphitization at a graphitization temperature of 2800° C. for 8 h to obtain a graphite negative electrode precursor;
[0041] (3) The above-mentioned graphite negative electrode precursor and coal tar powder (D50 is 8 μm) are placed in an agate mortar for mixing and coating, and the mass ratio of the graphite negative electrode precursor to the coal tar powder is 98:2. Then, the mixture is placed in a box-type atmosphere furnace for carbonization sintering. Under nitrogen protection, the temperature is increased to 1200°C at a heating rate of 1°C / min, and the mixture is kept warm for 4 hours. Finally, the mixture is passed through a 325-mesh sieve to obtain the graphite negative electrode material.
[0042] Example 4
[0043] This embodiment provides a method for preparing a high-rate graphite negative electrode material, which specifically includes the following steps:
[0044] (1) 100 g of needle coke was crushed to a particle size D50 of 10 μm, added to 300 mL of H2O2 with a mass concentration of 20%, mixed by magnetic stirring for 1 h, and then placed in a reactor, and then placed in an oven at 80° C. for 2 h. After the mixture was dried, filtered, washed with deionized water, and dried to obtain oxidized needle coke;
[0045] (2) dispersing the above-mentioned oxidized needle coke in petroleum ether, adding triethylamine and 2-bromoisobutyryl bromide, the mass ratio of oxidized needle coke, triethylamine and 2-bromoisobutyryl bromide is 100:5:1, stirring and reacting for 12 hours, filtering, washing, and obtaining bromine-functionalized oxidized raw coke; re-dispersing the bromine-functionalized oxidized raw coke in petroleum ether, adding cuprous bromide, 4-vinylbenzene boronic acid and pentamethyldivinyltriethylamine under nitrogen protection, the mass ratio of oxidized needle coke, cuprous bromide, 4-vinylbenzene boronic acid and pentamethyldivinyltriethylamine is 100:0.15:1:0.15, stirring and reacting for 24 hours, filtering, washing, and drying to obtain oxidized raw coke with surface chemical grafting of polystyrene boric acid;
[0046] (3) placing the above-mentioned oxidized raw material coke with surface chemical grafting of polystyrene boric acid in a box-type atmosphere furnace for pre-carbonization sintering, heating to 900°C at a heating rate of 3°C / min under nitrogen protection, keeping the temperature for 4 hours, and then placing it in a graphitization furnace for high-temperature graphitization at a graphitization temperature of 2900°C for 6 hours to obtain a graphite negative electrode precursor;
[0047] (4) The above-mentioned graphite negative electrode precursor and coal tar powder (D50 is 6 μm) are placed in an agate mortar for mixing and coating, and the mass ratio of the graphite negative electrode precursor to the coal tar powder is 95:5. Then, the mixture is placed in a box-type atmosphere furnace for carbonization sintering. Under nitrogen protection, the temperature is increased to 1150°C at a heating rate of 3°C / min, and the mixture is kept warm for 6 hours. Finally, the mixture is passed through a 325-mesh sieve to obtain the graphite negative electrode material.
[0048] Comparative Example 1
[0049] This comparative example proposes a method for preparing a high-rate graphite negative electrode material, which specifically comprises the following steps:
[0050] (1) After 100 g of needle coke was crushed to a particle size D50 of 10 μm, it was placed in a box-type atmosphere furnace for pre-carbonization sintering, and under nitrogen protection, the temperature was increased to 900° C. at a heating rate of 3° C. / min, and kept at this temperature for 4 h. Then, it was placed in a graphitization furnace for high-temperature graphitization at a graphitization temperature of 2900° C. for 6 h to obtain a graphite negative electrode precursor;
[0051] (2) The above-mentioned graphite negative electrode precursor and coal tar powder (D50 is 6 μm) are placed in an agate mortar for mixing and coating, and the mass ratio of the graphite negative electrode precursor to the coal tar powder is 95:5. Then, the mixture is placed in a box-type atmosphere furnace for carbonization sintering. Under nitrogen protection, the temperature is increased to 1150°C at a heating rate of 3°C / min, and the mixture is kept warm for 6 hours. Finally, the mixture is passed through a 325-mesh sieve to obtain the graphite negative electrode material.
[0052] Comparative Example 2
[0053] This comparative example proposes a method for preparing a high-rate graphite negative electrode material, which specifically comprises the following steps:
[0054] (1) 100 g of needle coke was crushed to a particle size D50 of 10 μm, added to 300 mL of H2O2 with a mass concentration of 20%, mixed by magnetic stirring for 1 h, and then placed in a reactor, and then placed in an oven at 80° C. for 5 h. After the mixture was dried, filtered, washed with deionized water, and dried to obtain oxidized needle coke;
[0055] (2) placing the oxidized needle coke in a box-type atmosphere furnace for pre-carbonization sintering, heating the temperature to 900°C at a heating rate of 3°C / min under nitrogen protection, keeping the temperature for 4 hours, and then placing it in a graphitization furnace for high-temperature graphitization at a graphitization temperature of 2900°C for 6 hours to obtain a graphite negative electrode precursor;
[0056] (3) The above-mentioned graphite negative electrode precursor and coal tar powder (D50 is 6 μm) are placed in an agate mortar for mixing and coating, and the mass ratio of the graphite negative electrode precursor to the coal tar powder is 95:5. Then, the mixture is placed in a box-type atmosphere furnace for carbonization sintering. Under nitrogen protection, the temperature is increased to 1150°C at a heating rate of 3°C / min, and the mixture is kept warm for 6 hours. Finally, the mixture is passed through a 325-mesh sieve to obtain the graphite negative electrode material.
[0057] Comparative Example 3
[0058] This comparative example proposes a method for preparing a high-rate graphite negative electrode material, which specifically comprises the following steps:
[0059] (1) 100 g of needle coke was crushed to a particle size D50 of 10 μm, and then mixed with epoxy resin (hard carbon material) at a mass ratio of 100:2. The mixture was placed in a drum furnace for heating and granulation at a temperature of 100° C. After the granulation was completed, needle coke coated with a hard carbon layer was obtained;
[0060] (2) placing the needle coke coated with the hard carbon layer in a box-type atmosphere furnace for pre-carbonization sintering, heating to 900°C at a heating rate of 3°C / min under nitrogen protection, keeping the temperature for 4 hours, and then placing it in a graphitization furnace for high-temperature graphitization at a graphitization temperature of 2900°C for 6 hours to obtain a graphite negative electrode precursor;
[0061] (3) The above-mentioned graphite negative electrode precursor and coal tar powder (D50 is 6 μm) are placed in an agate mortar for mixing and coating, and the mass ratio of the graphite negative electrode precursor to the coal tar powder is 95:5. Then, the mixture is placed in a box-type atmosphere furnace for carbonization. Under nitrogen protection, the temperature is increased to 1150°C at a heating rate of 3°C / min, and the mixture is kept warm for 6 hours. Finally, the mixture is passed through a 325-mesh sieve to obtain the graphite negative electrode material.
[0062] The graphite negative electrode material, conductive carbon black, and binder polyvinylidene fluoride (PVDF) prepared in the above embodiment or comparative example are stirred and mixed in a mass ratio of 91.5:2:6.5, wherein PVDF is dissolved with an appropriate amount of N-methylpyrrolidone (NMP); the mixed slurry is evenly coated on a previously prepared copper foil, and after being baked in a vacuum drying oven at 110° C. for 12 h, it is weighed and used as the negative electrode of a simulated battery, a metal lithium sheet is used as a counter electrode, a diaphragm is Celgard 2400, and an electrolyte is a 1 mol / L LiPF6 solution (EC:DMC volume ratio is 1:1 as a solvent), and assembled into a button battery CR 2016 in a deoxygenated and dehydrated glove box filled with argon.
[0063] The charge and discharge test of button batteries was carried out on the battery test system of Wuhan Blue Electric Electronics Co., Ltd., at room temperature, with constant current charge and discharge, and the charge and discharge voltage was limited to 0.005-2V. The results are shown in Table 1 below:
[0064] Table 1 Electrical performance results of the graphite negative electrode materials described in the examples and comparative examples
[0065]
[0066] In Table 1 above, compared with Comparative Example 1, Example 1 omits the surface oxidation treatment in the latter. Since a hard carbon coating layer cannot be formed on the graphite surface, its cycle performance and first-efficiency performance are reduced; compared with Comparative Example 2, Example 1 has a longer oxidation treatment time and a deeper pre-oxidation degree. Since the hard carbon coating layer formed is thicker, the first efficiency and energy density are lower; compared with Comparative Example 3, Example 1 mixes the raw coke with the hard carbon coating agent to form a hard carbon coating layer. Since the hard carbon coating layer is not directly formed in situ, the effect of improving the cycle stability of the graphite negative electrode is limited.
[0067] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a high-rate graphite negative electrode material, characterized in that: The steps include: S1. After the raw coke is subjected to oxidation treatment, the surface of the raw coke is oxidized to obtain oxidized raw coke; S2, pre-carbonizing and graphitizing the oxidized raw coke to form graphite with a hard carbon layer on the surface, thereby obtaining a graphite negative electrode precursor; S3, mixing the graphite negative electrode precursor with the asphalt material, and then carbonizing and sintering, so that a soft carbon coating layer is further formed on the surface of the hard carbon coating layer, and a soft and hard carbon coated graphite material is obtained, which is the graphite negative electrode material.
2. The method for preparing a high-rate graphite negative electrode material according to claim 1, characterized in that: In step S1, the raw coke is at least one of needle coke, petroleum coke, asphalt coke or calcined coke; and the oxidant is at least one of hydrogen peroxide, potassium permanganate, sodium hypochlorite or manganese dioxide.
3. The method for preparing a high-rate graphite negative electrode material according to claim 1 or 2, characterized in that: In step S1, the oxidation treatment temperature is 60-90°C and the time is 1-3h.
4. The method for preparing a high-rate graphite negative electrode material according to any one of claims 1 to 3, characterized in that: In step S2, the pre-carbonization sintering temperature is 800-1000°C, the time is 3-6h, and the heating rate is 1-5°C / min; the graphitization sintering temperature is 2800-3000°C, and the time is 4-8h; Preferably, the pre-carbonization and graphitization sintering are performed under the protection of nitrogen or argon.
5. The method for preparing the high-rate graphite negative electrode material according to any one of claims 1 to 4, characterized in that: In step S3, the asphalt material is at least one of coal asphalt, petroleum asphalt or mesophase asphalt; Preferably, the mass ratio of the graphite negative electrode precursor to the asphalt material is 93-98:2-7.
6. The method for preparing the high-rate graphite negative electrode material according to any one of claims 1 to 5, characterized in that: In step S3, the carbonization sintering temperature is 1000-1200°C, the time is 4-8h, and the heating rate is 1-5°C / min.
7. The method for preparing a high-rate graphite negative electrode material according to any one of claims 1 to 6, characterized in that: Before step S2, the process also includes chemically grafting polystyrene boric acid onto the surface of the oxidized raw coke; Preferably, the "chemically grafting polystyrene boric acid on the surface of the oxidized raw coke" specifically comprises: subjecting the oxidized raw coke to a condensation reaction with 2-bromoisobutyryl bromide to obtain bromine-functionalized oxidized raw coke, and then subjecting the oxidized raw coke to a surface-initiated free radical polymerization reaction with 4-vinylbenzeneboronic acid to obtain the oxidized raw coke with polystyrene boric acid chemically grafted on the surface; Preferably, the mass ratio of the oxidation raw material coke to 4-vinylbenzeneboric acid is 100:0.5-2.
8. A high-rate graphite negative electrode material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
9. The high-rate graphite negative electrode material according to claim 8, characterized in that: The graphite negative electrode material comprises graphite, a hard carbon layer coated on the surface of the graphite and a soft carbon layer coated on the surface of the hard carbon layer.
10. A lithium ion battery, characterized in that: It comprises the graphite negative electrode material according to claim 8 or 9.
Citation Information
Cited By
Lithium ion battery negative electrode material precursor, preparation method thereof and pre-carbonization furnace
CN121020549A
Preparation method of graphite composite material
CN121672515A
Modified graphite material, preparation method thereof and battery
CN122314757A